The Mizne-Blumental Collection - Dissentshik, Ronnie; Guralnik, Nehama; Calo, Emanuela; Cohen, Olga; Feldmann, Ruth; Israel, Ahuva; Yifat, Dorit (Tel Aviv : Tel Aviv Museum of Art, 1995)
Braque, Georges ; Brauner, Victor ; Campigli, Massimo ; De Chirico, Giorgio ; Dali, Salvador ; Delaunay, Robert ; van Doesburg, Theo ; van Dongen, Kees ; Dubuffet, Jean ; Dufy, Raoul ; Ernst, Max ; Fautrier, Jean ; Forain, Jean-Louis ; Foujita, Tsuguharu ; Friesz, Emile-Othon ; Gleizes, Albert ; Gontcharova, Natalia ; Gris, Juan ; Hodler, Ferdinand ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Klimt, Gustav ; de Kooning, Willem ; Larionov, Mikhail ; Laurencin, Marie ; Leger, Fernand ; Magritte, René ; Marcoussis, Louis ; Mondriaan, Piet ; Nicholson, Ben ; Ozenfant, Amédée ; Pevsner, Antoine ; Picasso, Pablo ; Severini, Gino ; Sutherland, Graham ; Tanguy, Yves ; Torres-Garcia, Joaquin ; de Toulouse-Lautrec, Henri ; Vasarely, Victor ; de Vlaminck, Maurice
biografie, bibliografie
Engels
boek